Locus of Control Personality of Women Leaders as a Moderator Influencing Personality Traits of Women Leaders on Employee Performance in the Sharia-Based Banking Industry in Makassar City - Ceskakusumadewi Baharuddin; Jeni Kamase; Bahar Sinring; Roslina Alam (Budapest International Research and Critics University, 2021)
Recently researchers found that there are no significant differences in leadership abilities between males and females in executive positions emerged. Therefore there is no significant difference in personality between men and women in executive positions in improving employees' performance. This research will be focus on women executives (leaders) personality traits on improving employees' performance. This research aims to investigate the influence of personality traits of women leaders moderated by their locus of control on employee performance in the sharia-based banking industry in Makassar city. This research is going to use the big five model personality, self-efficacy, Machiavellian, and narcissism to analyze personality traits of women executive and also as independent variables. Employees' performances are going to be the dependent variable. And locus of control of the women executive is going to use as moderating variable that could possibly improve the relationship between the personality traits of the female executive on employees' performance. The sample of this research is 40 women executives (from supervisors to managers) in the sharia-based banking industry in Makassar city. The data of this research are collected by questioners. Then the data are going to be analyzed with SEM-PLS statistic. The statistical data gathered during the research revealed that internal locus of control of women leaders’ moderate relationship between big five model personality, self-efficacy, machiavellian, and narcissitic personality of women leaders on employee performance in the sharia-based banking industry in Makassar city. Thus, this research results prove that locus of control could moderate in improving the relationship between personality traits of women leaders on improving employees performance but only internal locus of control of women leader not the external locus of control of women leader.